2017
DOI: 10.3389/fcimb.2017.00262
|View full text |Cite
|
Sign up to set email alerts
|

The Intestinal Eukaryotic and Bacterial Biome of Spotted Hyenas: The Impact of Social Status and Age on Diversity and Composition

Abstract: In mammals, two factors likely to affect the diversity and composition of intestinal bacteria (bacterial microbiome) and eukaryotes (eukaryome) are social status and age. In species in which social status determines access to resources, socially dominant animals maintain better immune processes and health status than subordinates. As high species diversity is an index of ecosystem health, the intestinal biome of healthier, socially dominant animals should be more diverse than those of subordinates. Gradual col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 94 publications
2
41
0
1
Order By: Relevance
“…For Ancylostoma duodenale , fecundity (the number of eggs/g feces per worm) is density‐dependent, declining from 287 eggs to approximately 100 eggs for the first 100 worms and then remains largely independent thereafter (Anderson & Schad, ); hence, FECs are a reasonable index of adult worm infection load. Also, Heitlinger et al () found a significant positive correlation between egg or oocyst counts and the amount of parasite DNA in the feces for the taxa identified as Ancylostoma , Diphyllobothrium, and Coccidia in this study population. In pigs, Trichuris suis egg counts are deemed a reliable approximate estimate of the number of adult worms per host, that is, parasite load (Gassó et al, ).…”
Section: Methodssupporting
confidence: 58%
See 4 more Smart Citations
“…For Ancylostoma duodenale , fecundity (the number of eggs/g feces per worm) is density‐dependent, declining from 287 eggs to approximately 100 eggs for the first 100 worms and then remains largely independent thereafter (Anderson & Schad, ); hence, FECs are a reasonable index of adult worm infection load. Also, Heitlinger et al () found a significant positive correlation between egg or oocyst counts and the amount of parasite DNA in the feces for the taxa identified as Ancylostoma , Diphyllobothrium, and Coccidia in this study population. In pigs, Trichuris suis egg counts are deemed a reliable approximate estimate of the number of adult worms per host, that is, parasite load (Gassó et al, ).…”
Section: Methodssupporting
confidence: 58%
“…This suggests the intriguing idea that the fitness cost of a more diverse GI parasite community may be lower than one dominated by a limited number of taxa. Previously, we found that the eukaryome in high‐ranking hyenas is more diverse than that of low‐ranking animals (Heitlinger et al, ) which may indicate that high‐ranking animals have a more diverse, stable, and ecologically “healthy” GI community than low‐ranking animals.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations